Archives Management and Service Delivery at Caritas in Kabale. - Nyangoma, Linet (Kabale University, 2025)
This study explores the impact of archives management on service delivery at Caritas in Kabale District. Effective archives management facilitates access to information, enhances decision-making, and improves overall service delivery in organizations. The specific objectives include assessing current archival management practices at Caritas, identifying challenges that hinder effective archives management, and proposing strategies to overcome these challenges. Through qualitative and quantitative methods, the research revealed that while Caritas employs several archival management practices, issues such as inadequate training, limited resources, and insufficient technological support significantly impede efficiency. The study also highlights the critical role of proper archives management in enhancing service delivery, underscoring the need for strategic interventions. Recommendations include investing in staff training, improving technological infrastructure, and establishing clear policies for records management. Overall, this study emphasizes that robust archives management is integral to optimizing service delivery at Caritas, contributing to more effective humanitarian efforts in the community.